Comprehensive food security and vulnerability analysis: Nigeria - Kuku, Oluyemisi; Mathiassen, Astrid; Wadhwa, Amit; Myles, Lucy; Ajibola, Akeem (International Food Policy Research Institute, 2013)
The Nigerian Comprehensive Food Security and Vulnerability Analysis (CFSVA) provides an in-depth assessment of the food security situation within Nigeria. This is very important as it equips policymakers with timely and relevant information that will aid the targeting of interventions.